Precipitation affects soil microbial and extracellular enzymatic responses to warming. (May 2018) - Li, Guanlin; Kim, Seongjun; Han, Seung Hyun; Chang, Hanna; Du, Daolin; Son, Yowhan
Abstract: Soil microbial communities and extracellular enzymes have important roles in many terrestrial ecosystem processes and are influenced by climate change drivers. In the present study, the individual and/or interactive effects of climate change drivers on soil microbial communities and extracellular enzyme activities were measured in experimental field plots planted with Pinus densiflora and subjected to air warming (ambient or +3 °C) in combination with precipitation treatments (reduced by 30%, ambient or elevated by 30%). Soil microbial biomass and four extracellular enzyme activities were measured. Additionally, the structure and composition of microbial communities were assessed. Warming increased microbial biomass nitrogen concentration by 22.3% in precipitation control plots and by 17.9% in elevated precipitation plots. Warming lowered the extracellular enzyme activity in precipitation control plots, but increased their activity in elevated precipitation plots. Warming had a differential effect on the composition of bacterial and fungal communities under different precipitation treatments, with significant changes in therelative abundance of Proteobacteria and Acidobacteria. Meanwhile, the alpha diversity index of both bacterial and fungal communities were affected by warming, with variation among the precipitation treatments. Changes in enzyme activities and microbial communities were correlated with shifts in soil environmental conditions (e.g., moisture, temperature, and available nutrients). In conclusion, changes in soil environmental conditions may select for distinct soil microbial communities, further reshaping soil ecosystem processes and functions in a warmer world. Graphical abstract: Highlights: Effects of climate change on soil microbial communities and enzymes were assessed. Precipitation significantly affected the diversity of soil fungal communities. Precipitation modified the response of soil microbial communities and enzymes to warming. Microbial responses to climate change may be reliant on soil environmental conditions.